Antioxidant and protective effect of Stachys pilifera Benth against nephrotoxicity induced by cisplatin in rats. Issue 5 (10th March 2020) - Sadeghi, Hossein; Mansourian, Mahboubeh; Panahi kokhdan, Esmaeel; Salehpour, Zeinab; Sadati, Iman; Abbaszadeh‐Goudarzi, Kazem; Asfaram, Arash; Doustimotlagh, Amir Hossein
Abstract: The aim of current study was to assess the antioxidant and renoprotective effects of Stachys pilifera Benth ( S.P.B. ) hydroalcoholic extract on nephrotoxicity induced with cisplatin (CP). Adult rats with bodyweight of 180–220 g were divided into five groups ( n = 7) treated as follows: group 1, control; group 2, CP; group 3, pretreatment with S.P.B. before CP; group 4, posttreatment with S.P.B. after CP; and, group 5, S.P.B. extract . A single dose of CP (7 mg/kg) was intraperitoneally injected on the fifth day and hydroalcoholic extract of S.P.B. (500 mg kg –1 day –1 ) was orally administered. The levels of oxidative stress markers, biochemical tests, and histopathological staining were assayed in serum and renal tissue. Also, the chemical composition of S.P.B. extract was determined by GC‐MS analysis. The main compositions of S.P.B. extract identified by GC‐MS analysis, were hexadeca‐2, 6, 10, 14‐tetraen‐1‐ol, 3, 7, 11, 16‐tetramethyl (24.77%), thymol (14.1%), and linolenic acid (13.4%). In groups treated and pretreated with S.P.B., blood urea nitrogen, creatinine, malondialdehyde, and nitric oxide metabolite in serum as well as malondialdehyde and protein carbonyl content of kidney tissues were significantly decreased in comparison to CP group; in contrast, total thiol group showed a significant increase in treated group as compared to CP group. Furthermore, histological investigation indicated that treatment with S.P.B. improved renal damages induced by CP. The current study showed that S.P.B. hydroalcoholic extract improved the biochemical parameters and kidney function as well as restored antioxidant activity in CP‐induced nephrotoxicity. However, it needs more investigations to define the mechanism of S.P.B. action. Practical applications: In different regions of Iran, Stachys is demonstrated by 34 species, out of which 13 are endemic, one of these endemic species is Stachys pilifera Benth ( S.P.B. ) . The oil of S.P.B. is mainly consisted of cis ‐chrysanthenyl acetate, cis ‐chrysanthenol, spathulenol, β‐caryophyllene, linalool, and terpinen‐4‐ol. Moreover, phytochemical studies have shown the presence of compounds such as diterpenes, phenylethanoid glycosides, saponins, terpenoides, and flavonoids in Stachys species. The aerial parts of S.P.B. are consumed as herbal tea to treat several disorders, for example, infections, asthma, and rheumatoid arthritis in Iranian folk medicine. The aim of current study was to evaluate the antioxidant and protective effects of S.P.B. hydroalcoholic extract on nephrotoxicity induced with cisplatin (CP). The current study showed that S.P.B. hydroalcoholic extract improved the biochemical parameters and kidney function as well as restored antioxidant activity in CP‐induced nephrotoxicity. However, it needs more researches to define the mechanism of S.P.B. action. Abstract : The aim of the current study was to assess the antioxidant and renoprotective effects of Stachys pilifera Benth (S.P.B) hydroalcoholic extract on nephrotoxicity induced with cisplatin (CP). The results showed that S.P.B hydroalcoholic extract improved the biochemical parameters and kidney function as well as restored antioxidant activity in CP‐induced nephrotoxicity.